Jh̃āśīcī rāṇī, āṇi sattāvana sālacyā baṇḍācẽ aitihāsika kārya - Haḍapa, Viṭhṭhala Vāmana, 1900-1960 (SAMP early 20th-century Indian books project ;, 1940)
On Lakshmi Bai, Rani of Jhansi, d. 1858 and Sepoy Rebellion, 1857-1858.